The influence of leader power on interpersonal conflict among employees of Government Linked Companies, Malaysia / Rozilah Abdul Aziz ... [et al.] - Abdul Aziz, Rozilah; Hassan, Narehan; Noranee, Shereen; Ali, Sharrifah; Abdul Razak, Nurfadzilah (Universiti Teknologi Mara Selangor, 2016)
Organizational conflict is partly depended on the magnitude of power exercised by superiors in the workplace. The need to investigate how manager’s power affects subordinates’ interpersonal conflict is crucial so that managers can change or maintain their power to achieve optimum result in organization. Hence, the purpose of this study is to examine the influence of leader power towards interpersonal conflict at Government Linked Companies (GLCs), Malaysia. A total of 388 questionnaires were distributed to employees of GLCs, Malaysia. A Structural Equation Modelling (SEM) analysis revealed that forty-one percent of the variation in interpersonal conflict can be explained by the power possessed by managers. It also revealed there is a strong positive, linear and significant relationship between leader power and interpersonal conflict. Therefore, management should be concerned with the authority given to managers as power could lead to a devastating interpersonal conflict.